The study of dynamic resource allocation on aggregation of unlicensed spectrum in LTE-A networks. Issue 1 (7th April 2022) - Wu, Jung-Shyr
The 3GPP formulated the fourth-generation LTE-Advanced specifications, in which Carrier Aggregation technology can increase the data transmission rate by aggregating continuous and non-continuous carriers to meet the transmission needs of a large number of users. However, users' demand for multimedia network application services continues to increase and makes the licensed spectrum more and more overwhelming. Therefore, this article hopes to combine the licensed and unlicensed spectrum to provide a wider data channel with higher data transmission. We focus on improving the throughput of the downlink system, and propose a genetic algorithm to optimise the weights which referring to the carrier unit channel quality and load conditions to select the most suitable carrier unit for the user. Afterwards, resource allocation methods are presented for the different traffic of GBR and Non-GBR effectively. Finally, we show the simulation results to prove that the proposed method is effective in improving system throughput and user satisfaction.